QUANTITATIVE PHOSPHOPROTEOMIC ANALYSIS OF T CELL RECEPTOR SIGNALING IN DIABETES PRONE AND RESISTANT MICE - Iwai, Leo K. (2010)
Type 1 diabetes, in human patients and NOD mice, results from immune attack on insulin-producing beta-cells of the pancreas by autoreactive T lymphocytes. In NOD mice, genetically-controlled perturbations in the signaling pathways downstream of the antigen-specific T cell receptor (TCR) may be instrumental in the altered responses of T cells, manifest as inefficient induction of apoptosis after recognition of self-antigens in the thymus, or as perturbed reactivity of mature T cells in peripheral organs. To map this signaling difference(s), we have used mass spectrometry-based quantitative phosphoproteomics to compare the activation of primary CD4(+) T cells of diabetes-prone NOD and -resistant B6.H2g7 mice. Immunoprecipitation and IMAC purification of tyrosine-phosphorylated peptides, combined with a stable-isotope iTRAQ labeling, enabled us to identify and quantify over 77 phosphorylation events in 54 different proteins downstream of TCR stimulation of primary CD4(+) T cells. This analysis showed a generally higher level of phosphotyrosine in activated NOD cells, as well as several phosphorylation sites that appeared to be differentially regulated in these two strains (involving TXK, CD5, PAG1, and ZAP-70). These data highlight the differences in signaling between CD4(+) T cell compartments of NOD and B6g7 mice, and may underlie the dysregulation of T cells in NOD mice.